Analyzing English Textbook through the Lens of Tomlinson’s Theory - Abdul Syahid; Muliana Setia Hapsari ; Siti Anisah ; Tiara Nur Fatimah Almadani; Windy Annastasia Maharani (International Journal of Educational Technology and Society, 2024)
This study examines the English textbook "English Class X for SMA/MA/SMK/MAK Revised Edition 2017" through the lens of Tomlinson's theoretical framework to ascertain its effectiveness in facilitating language acquisition. Using a descriptive approach and document analysis, the study focused on book contents, examining elements such as impact, learner comfort, confidence building, relevance, language exposure and more. Data collection involved examining the content of the textbook, while analysis included subjective and objective ratings based on Tomlinson's sixteen criteria for effective learning materials. Results showed that the textbook was generally in line with Tomlinson's standards, meeting fifteen of the sixteen criteria, including impactful materials, learner engagement, and diverse learning opportunities. However, the textbook was lacking in facilitating learner self-investment. In addition, the study suggests improvements in physical design to enhance attractiveness. The textbook "English Class X" overall meets the criteria as a quality learning resource with diverse and engaging content, supporting effective language learning. This analysis provides important insights for informed textbook selection that fit within a pedagogical framework, aiming to improve student learning outcomes.